Vertical patterns of epiphytic bryophyte diversity in a montane Nothofagus forest in the Chilean Andes. Issue 4 (2nd October 2017) - Mellado-Mansilla, Daniela; León, Carolina A.; Ortega-Solís, Gabriel; Godoy-Güinao, Javier; Moreno, Ricardo; Díaz, Iván A.
ABSTRACT: Epiphytic bryophytes are an important component of many forest ecosystems. Several studies have reported vertical distribution patterns for this species, finding many taxa growing along the entire vertical profile of host trees, some in the most exposed upper areas of the canopies. Many studies in Chilean forests have focused on epiphytes, but most of them were located in lowland and coastal forests. This study is the first scientific exploration of the epiphytic communities that occupy the entire vertical profile of large Nothofagus dombeyi (Mirb.) Oerst. trees in a montane Nothofagus forest in the Chilean Andes (39°25′S). Our goals were (i) to describe the richness of the epiphytic species inhabiting large N. dombeyi trees, (ii) to evaluate differences in composition related to the height, azimuth and diameter of each host tree, and (iii) to explore the distribution of epiphytic species within the vertical profile of trees. We climbed 10 large N. dombeyi trees located between 940 and 1190 m in altitude. All epiphytes were sampled every meter, from the base up to the highest climbable branch. The epiphytic community was dominated by non-vascular epiphytes, with 17 taxa, all of which were bryophytes. Frullania rostrata, Gackstroemia aff. magellanica, Hypnum skottsbergii and Zygodon penstastichus were the most frequently observed taxa. Species composition varied with height on the tree, but no differences between trees were observed. The vertical distribution showed that three taxa were restricted to the crown, five were abundant throughout the whole vertical profile and four were restricted to the trunk close to the ground. The information here could be relevant due to the pressure to manage these Nothofagus forests, where the associated biodiversity is not even recorded in forestry inventories.